Literasi Politik Komunitas Samin di Bojonegoro dalam Pemilu Perspektif Fiqih Siyasah - Muh Fathoni Hasyim (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
The dynamics of political participation of the Samin community in Bojonegoro show significant development of political literacy. This study is focused on answering the political literacy of the Samin community in voicing their aspirations in the General Election from the perspective of Fiqh Siyasah. The results of the study show that the level of political literacy of the Samin community is increasing. The indicator is that the enthusiasm of the Samin people in exercising their voting rights in the general election. In facing elections, the Samin community usually holds a community meeting led by the customary head, to determine the direction of their political aspirations. Over time, this tradition, although still valid, the results of its decisions are not binding. This means that the Samin people are given the freedom to make their own choices. This is different from previous times where the results of the deliberations were a collective decision in determining political aspirations. In the context of Fiqh Siyasah, the political literacy of the Samin community in the General Election is an exciting process of democratization, because the participation of the Samin community shows a growing awareness of living as a nation and a state within the frame of diversity. The practice of deliberation carried out by the Samin community is the application of the principle of deliberation in Islam, so that even though the results are not binding, the decision-making process creates a dialogue between community members to build an increasingly dynamic and progressive political literacy of the Samin community.